Hubungan Tingkat Pengetahuan Kontak Serumah TB Terhadap Penerimaan Dan Kepatuhan Menjalankan Terapi Pencegahan Tuberkulosis - Susanti, Ida; Rizqiea, Noerma Shovie; Azali, Lalu M.Panji (MEDIA ILMU KESEHATAN, 2025)
Background: Indonesia ranks second globally in tuberculosis (TB) burden, with 1,060,000 cases reported in the 2023 Global TB Report. Household contact coverage for Tuberculosis Preventive Therapy (TPT), a key program indicator, remains below target, primarily due to limited knowledge among household contacts regarding TPT.Objective: This study aims to examine the relationship between the level of knowledge of household contacts of TB patients and their acceptance and adherence to the TPT program in the working area of Klego Community Health Center.Methods: The research utilized an analytic observational quantitative study with a cross-sectional design. Purposive sampling was employed to select 49 respondent’s household contacts of TB.Results: The Gamma test results revealed a significance value of p-value = 0.003. The correlation coefficient Gamma (r) = 0.582Conclusion: There is a significant relationship between the level of knowledge of household contacts of TB patients and their acceptance and adherence to the TPT program in the working area of Klego Community Health Center. The correlation is of moderate strength and positive in nature, indicating that higher levels of knowledge among household contacts are associated with greater acceptance and adherence to the TPT program